JES 2020
DOI: 10.31045/jes.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in the Preparation of University Supervisors: Dual Perspectives from Supervisors and Administrators

Abstract: Prior research shows that supervisors of teacher candidates are typically underprepared for their work and receive little oversight of it. However, there has been less research into these causes and the effects of minimal preparation on supervisors. This case study of a teacher education department uses survey, interviews, and document analysis to examine the tensions that occur when supervisors are underprepared for their roles. The results indicate three tensions that undermine supervisors' practice: unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…First, because all faculty roles have shifted and now, given AACTE's (2018) definition of supervision, include the supervision of PSTs to some extent, preparation for all faculty for these new or added role functions is imperative. This is even more crucial given the increasing complexity of the supervisor role (Burns et al, 2016b), the plethora of pedagogical skills supervisors need (Burns & Badiali, 2015), and the dearth of training for traditional university supervisors (Baecher et al, 2014;Capello, 2020;Levine, 2011;Slick, 1998). Several key elements need to be in place for the school-university partnership to function effectively, one of which is that all teacher educators at the school and university sites should have a clear understanding of how to foster PST growth and the pedagogy guiding their practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, because all faculty roles have shifted and now, given AACTE's (2018) definition of supervision, include the supervision of PSTs to some extent, preparation for all faculty for these new or added role functions is imperative. This is even more crucial given the increasing complexity of the supervisor role (Burns et al, 2016b), the plethora of pedagogical skills supervisors need (Burns & Badiali, 2015), and the dearth of training for traditional university supervisors (Baecher et al, 2014;Capello, 2020;Levine, 2011;Slick, 1998). Several key elements need to be in place for the school-university partnership to function effectively, one of which is that all teacher educators at the school and university sites should have a clear understanding of how to foster PST growth and the pedagogy guiding their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Mette and colleagues posited that supervision is formative for the purpose of "professional growth" and evaluation is summative for the "assessment of performance" and should factor into administrative and employment decisions (Mette et al, 2017, p. 710;Mette et al, 2020;Mette & Riegel, 2018). Recent research has documented the conflation of evaluation and supervision specifically within teacher education (Burns & Badiali, 2015;Glickman et al, 2014;Palmeri & Peter, 2019) and found that tensions exist for PST supervisors between these tasks (Burns & Badiali, 2015;Capello, 2020). Unfortunately, recent federal and state accountability policies and frameworks for in-service teachers and PSTs such as Race to the Top, ESSA, the Danielson framework, the Marzano framework, and edTPA have created an educational culture that emphasizes high-stakes evaluation over instructional supervision to foster teacher growth (Burns & Badiali, 2015), conflates formative and summative feedback (Mette et al, 2020), and forces supervisors into evaluative roles (Mette et al, 2017) even though an undue supervisory focus on evaluation is detrimental to building relationships with PSTs, risk-taking, meaning making, and PST growth (Burns & Badiali, 2015;Ochieng' Ong'ondo & Borg, 2011).…”
Section: The Changing Role Of the Supervisor Due To The Expansion Of mentioning
confidence: 99%
“…Similarly, Mentor teacher support, feedback, and evaluation (Capello, 2020, Selçuk, &Yöntem, 2019, Ali, Othman, & Karim, 2018 help prospective teachers to enhance their skills during teaching practicum. The same findings were received through the given study, which supports the stated idea.…”
Section: Discussionmentioning
confidence: 99%
“…This approach deviates from the conventional teaching supervision of student teachers. [11], [19], [20], [27], [30], [39], [40], [41] Mentoring, Coaching, and Consulting…”
Section: A Methods For Developing a Competency-based Online Supervisi...mentioning
confidence: 99%
“…The process of teaching supervision encompasses several sequential stages: initial planning supervision, in-school supervision, provision of guidance and recommendations, enhancement of teaching methodologies, culminating in supervisory assessment [19]. The role of in-service professors is one of the roles of university professors who must act as in-service professors, mentors, and trainers [20]. Furthermore, the establishment of a strong rapport with the broader social community and the continual development of professional competencies are pivotal components for student growth and success [21].…”
Section: Teaching Supervision On the Competency Base Of Pre-service T...mentioning
confidence: 99%